2000
DOI: 10.4049/jimmunol.165.12.7050
|View full text |Cite
|
Sign up to set email alerts
|

Fab Chains As an Efficient Heterodimerization Scaffold for the Production of Recombinant Bispecific and Trispecific Antibody Derivatives

Abstract: Due to their multispecificity and versatility, bispecific Abs (BsAbs) are promising therapeutic tools in tomorrow’s medicine. Especially intermediate-sized BsAbs that combine body retention with tissue penetration are valuable for therapy but necessitate expression systems that favor heterodimerization of the binding sites for large-scale application. To identify heterodimerization domains to which single-chain variable fragments (scFv) can be fused, we compared the efficiency of heterodimerization of CL and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…11 To evaluate CH1-CK heterodimerization strength in the context of 4Dm2m, we subcloned the N-terminal region of 4Dm2m, resulting in a heterodimeric construct (designated MD) composed of mD1.22-CH1 and m36.4-CK with total calculated molecular weight (cMW) of 52 kDa (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 To evaluate CH1-CK heterodimerization strength in the context of 4Dm2m, we subcloned the N-terminal region of 4Dm2m, resulting in a heterodimeric construct (designated MD) composed of mD1.22-CH1 and m36.4-CK with total calculated molecular weight (cMW) of 52 kDa (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Another previous study demonstrated that the use of Fab, but not CH1-CK, as a dimerization scaffold led to efficient production of bispecific and trispecific antibodies. 11 This prompted us to engineer CH1-CK to compensate for the loss of heterodimerization strength contributed by VH-VL. By combining structureguided design and library selection technologies, we identified six CH1-CK mutants that resulted in formation of more stable heterodimers of the MD variants than the wild-type MD (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, even simple scFv constructs cannot be expressed at high levels in mammalian cells; however, we have had considerable success in producing IgG or Fab fragments with high productivity in myeloma cultures. Since the low yield of hBS14 was likely due to its lack of the C H 1 domain, which is critical for the folding and transporting of IgG, we decided to develop an alternative type of trivalent bsMAb, based on the ''tribody'' design, 110 where two scFvs derived from the variable domains of hMN-14 are fused to h679 Fab. Once again, several varieties were generated by having an hMN-14 scFv fused to the carboxyl terminal end of both the Fd and light chain of an h679 Fab fragment.…”
mentioning
confidence: 99%
“…To overcome this problem, a number of improvements could be made. The size can be increased by modifications such as PEGylation or the addition of an extra scFv [20,21]. By addition of protein domains like the human serum albumin, the interaction with the FcRn can be enabled [22].…”
Section: Introductionmentioning
confidence: 99%